Heavy Equipment Rental Schedule Report Application Using Visual Basic.Net and MySQL Database - Syerlie Annisa; Yurita Delvianti (Knowbase : International Journal of Knowledge in Database, 2021)
The heavy equipment business in Indonesia is again excited in line with the increasing demand for heavy equipment by various sectors such as the mining sector, the agro-industry sector, and the construction sector. PT. Petronesia Benimel is one of the business fields engaged in renting heavy equipment. The management of the heavy equipment rental schedule to other companies has been carried out using a computerized system, namely using the Microsoft Excel application which is still not optimal in integrating, calling and processing data at once. Using these applications independently results in the management of heavy equipment rental reports being constrained because tenant data and rental management are often out of sync. The application uses Visual Basic programming language and MySQL database supported by research and product development methods and waterfall development models. Based on the trial results of using a schedule report application that can make it easier for staff to manage heavy unit rental schedules from various partner companies (stakeholders) so that better reports are obtained.